2013
DOI: 10.1016/s0254-6272(13)60136-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of moxibustion treatment on cell apoptosis and expressions of heat shock protein and second mitochondrial activator of caspase in acute gastric mucosal lesion of rats

Abstract: The moxibustion treatment could alleviate the gastric mucosal lesion caused by anhydrous ethanol, induce the over-expressions of HSP60 and HSP70, and down-regulate the expression of Smac, which could suppress cell apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…It might induce a series of signal pathways and stress through heat shock proteins [22, 39], including the Akt pathway and ER stress, as shown in the present study. Although the effect of moxibustion in the whole body requires more evidence, moxibustion is a suitable technique for local heat therapy to stimulate self-healing, recovery, and innate defense mechanisms.…”
Section: Discussionmentioning
confidence: 59%
“…It might induce a series of signal pathways and stress through heat shock proteins [22, 39], including the Akt pathway and ER stress, as shown in the present study. Although the effect of moxibustion in the whole body requires more evidence, moxibustion is a suitable technique for local heat therapy to stimulate self-healing, recovery, and innate defense mechanisms.…”
Section: Discussionmentioning
confidence: 59%
“…Caspase-3 is a key mediator for apoptosis and Liu et al [34] determined that caspase-3 is play in apoptotic cell death in stress-induced ulcer rat model. Some studies have shown that caspase 3 expression has increased in experimentally gastric ulcer models [35][36][37][38]. We detected that IND induced to apoptosis by increasing caspase-3 expression in stomach tissue and NA administration prevented to this evaluate in caspase-3 expression.…”
Section: Discussionmentioning
confidence: 57%
“…In general, apoptosis is a type of organized cell self-destruction by a series of signal cascades that include numerous gene products and cytokines. Caspase-3 activation serves an important role in apoptosis, whilst the imbalance between Bcl-2 (anti-apoptotic) and Bax (pro-apoptotic) has been recognized as a signature of the acquisition of apoptosis resistance in cancer cells ( 42 , 43 ). In addition, p53, acting as a transcriptional factor, serves an important role in promoting apoptosis in response to various cellular stressors, including oncogene activation ( 44 ).…”
Section: Discussionmentioning
confidence: 99%